Design and in situ synthesis of a Cu-based porous framework featuring isolated double chain magnetic character - Dey, Chandan; Das, Raja; Saha, Binoy Krishna; Poddar, Pankaj; Banerjee, Rahul (Chemical Communications, 2011)
A Cu-based double chain MOF was synthesized in hydrothermal conditions using an in situ ligand formation method. This double chain MOF shows temperature dependent ferromagnetic (long range ordering) and antiferromagnetic (intra double chain) coupling. The magnetic behaviour originating from the individual double chain remains almost same even after structural collapse due to the removal of guest water molecules.